You ask (Journal of Parents and Teachers, 2025)
The article refers to two questions and the answers provided by people knowledgeable about the topic. First, it discusses whether one should have a home library, offering children an opportunity to spark their curiosity for reading. Secondly, it addresses the question of whether children should play chess from a young age.